Cigarette Smoking and Habits (2): Some Studies on Perception and Promoting Factors Among University Students (Journal of Science and Technology, 2016)
A survey using structured questionnaire was carried out among 100 randomly picked second year classes of business students of University of Brighton approved by a University of Brighton Ethical Committee. It was tested for reliability to ensure consistency using the Test Re-test method. Out of 100 students, 47 were male and 53, female. Also, from the same 100, 51 were non-smokers, 29 were smokers, and 20, ex-smokers. Total of respondents (Y=7, N=93) indicates that inhaling other peoples' smoke was not enjoyable so there is a general dislike. The major overall reason for liking smoking is because of its relaxation properties (mean=2.57). The main reason for starting smoking were friends smoked ascribed to ‘cool' and curiosity reason, though majority did not agree to this. Few subjects agreed that they started smoking because there parent smoked, had money to buy cigarettes and their girlfriend or boyfriend smoked. Two-way Analysis of Variance (ANOVA) gave no significant difference between males and females, smokers and ex-smokers and no significant interaction between gender and being a smoker/ex-smoker. Students know that smoking is very bad and dangerous to their health. They do know that stopping smoking will improve their health, but once they are hooked on it, it is very hard to quit.